2003
DOI: 10.1177/15353702-0322805-23
|View full text |Cite
|
Sign up to set email alerts
|

Donor Lung Pretreatment with Surfactant in Experimental Transplantation Preserves Graft Hemodynamics and Alveolar Morphology

Abstract: In experimental lung transplantation, the reduction of endogenous surfactant properties occurs after graft preservation and transplant reperfusion. The aim of this study was to evaluate the efficacy of donor lung pretreatment with exogenous surfactant on graft damage after ischemia and reperfusion. Fourteen (control group A, n = 8; study group B, n= 6) young female white pigs (mean weight 27 +/- 3.5 kg) were used in a newly developed autotransplantation model within situcold ischemia. In study group B, before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…An extensive search of the literature revealed that Demertzis et al (30) and right). This hypothesis is in accordance with the previously published finding of decreased serum nitric oxide, a well-established vasodilator, during lung transplantation (18). It is known that the PVRI can increase just from edema.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An extensive search of the literature revealed that Demertzis et al (30) and right). This hypothesis is in accordance with the previously published finding of decreased serum nitric oxide, a well-established vasodilator, during lung transplantation (18). It is known that the PVRI can increase just from edema.…”
Section: Discussionsupporting
confidence: 93%
“…Histologic Studies. A pulmonary biopsy was performed from the left upper lobe after thoracotomy, from the left lower lobe after 3 hrs of reperfusion (Group E) and from the left lower lobe of Group C. Every sample was examined histopathologically using both hematoxylin-eosin staining and Karnovsky's solution as previously described (18). Assessment was performed in a blinded fashion.…”
Section: Hematologic Values the Hematocrit Valuesmentioning
confidence: 99%
“…The most important consequence of these rapidly evolving ionic disturbances is the accumulation of intracellular Ca + , which initiates several damaging effects/actions. These include [ 22 - 24 ]: a) mitochondrial dysfunction, leading to a failure of aerobic energy metabolism and lactate accumulation, b) activation of mitochondrial and cytoplasmic nitric oxide synthase (NOS) and production of nitric oxide [ 25 ], c) activation of phospholipase A 2 , which liberates arachidonic acid (AA), which is then converted by cyclooxygenases (COX 1,2) to a number of deleterious prostanoids and by lipoxygenases (LTs) some of which are chemo-attractants for polymorphonuclear leukocyte and macrophage influx, and) activation of the calcium-activated cysteine protease calpain which is mediating axonal damage in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is worsened by preservation solution and ischemia reperfusion injury. 101,102 Shearing forces that produce stress on alveoli, epithelial and endothelial damage, and augmentation of the cytokine response are mechanisms for the alveolar injury seen during mechanical ventilation. 103 Given the similarity of the lung injury seen in organ donors with the acute respiratory distress syndrome, lung protective strategies used in the treatment of acute respiratory distress syndrome may prevent further lung injury in marginal lung donors.…”
Section: Pulmonary Considerationsmentioning
confidence: 99%